Pengaruh Keteladanan dan Kreativitas Pembelajaran Guru Akidah Akhlak terhadap Moderasi Agama Siswa - Masluri; A. Mufrod Teguh Mulyo (Fahima, 2022)
Islam, as the most prominent religion adopted by the majority of Indonesians, certainly has rules that refer to the benefit of Muslims. This study aims to: (1) find out the influence of teacher example on the cultivation of religious moderation in students, (2) know the influence of teacher Akidah Akhlak's learning creativity on the cultivation of religious moderation in students, and (3) knowing the influence of the example and creativity of moral teachers' learning on the cultivation of religious moderation in student. Correlational quantitative research in MAN Sukoharjo for the 2020/2021 Academic Year in May-July 2017. The population was 215 people, and the sample was 135 people, and Krejcie and Morgan used stratified simple random sampling. Data collection techniques use questionnaires, interviews, and observations. Data analysis techniques use descriptive analysis, Product Moment correlation, regression, t-test, F test, and R2 test. The study results that: (1) The influence of teacher example on the cultivation of religious moderation of class X MAN Sukoharjo students for the 2020/2021 Academic Year is evidenced by calculated value of thitung 7.868 > ttable 1.97, then Ho was rejected and accepted Ha. 2) The influence of teacher learning creativity on the cultivation of religious moderation in class X MAN Sukoharjo students for the 2020/2021 Academic Year with a calculated value of thitung 6,336 > ttabel 1.97, then Ho and accept Ha. 3) The influence of teacher exemplary and teacher learning creativity on the cultivation of religious moderation in class X MAN Sukoharjo students for the 2020/2021 Academic Year is proven through the Fhitung of 47,625 and significance values of 0.000. Research suggests that principals and teachers should be able to take the results of this study as a foundation and guideline in improving the exemplary and creativity of teacher learning in instilling religious moderation through methods of discussion, tourist work, group work, and others.